2013
DOI: 10.1016/j.nicl.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Accurate multimodal probabilistic prediction of conversion to Alzheimer's disease in patients with mild cognitive impairment

Abstract: Accurately identifying the patients that have mild cognitive impairment (MCI) who will go on to develop Alzheimer's disease (AD) will become essential as new treatments will require identification of AD patients at earlier stages in the disease process. Most previous work in this area has centred around the same automated techniques used to diagnose AD patients from healthy controls, by coupling high dimensional brain image data or other relevant biomarker data to modern machine learning techniques. Such studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
203
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(218 citation statements)
references
References 52 publications
(52 reference statements)
13
203
2
Order By: Relevance
“…In addition, the early diagnosis is also helpful for selecting suitable patients for clinical trials. Numerous studies [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20] use neuroimaging techniques to detect pathology associated with AD and to predict the MCI-to-AD conversion. Among them, structural magnetic resonance imaging (MRI) has been the most extensively used imaging modality in the detection and prediction of AD as it is widely available and offers good diagnostic accuracy with moderate costs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the early diagnosis is also helpful for selecting suitable patients for clinical trials. Numerous studies [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20] use neuroimaging techniques to detect pathology associated with AD and to predict the MCI-to-AD conversion. Among them, structural magnetic resonance imaging (MRI) has been the most extensively used imaging modality in the detection and prediction of AD as it is widely available and offers good diagnostic accuracy with moderate costs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the large inter-subject variability, MR images are usually spatially registered to a common space for comparison [14], [20], [23]. Different studies have used different registration techniques to align anatomies at different levels of detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EBM provides a simple and robust tool for investigating disease patterns and estimating patient stages in a fully data‐driven manner. In familial and sporadic Alzheimer's disease,8, 10 as well as frontotemporal dementia,11 EBMs have provided staging systems with predictive power at least as good as pattern matching techniques, for example 12, 13. In contrast to pattern matching, however, the EBMs provide uniquely fine‐grained temporal patterns of atrophy, enhancing disease understanding, and a well‐defined staging system for stratification.…”
Section: Introductionmentioning
confidence: 99%
“…51 Young et al developed a Gaussian predictive model integrating multimodal data gathered from volumetric magnetic resonance imaging, fludeoxyglucose positron emission tomography, determination of cerebrospinal fluid t-tau, p-tau, and aβ42 levels, and APOE genotyping, which correlated with conversion rates from MCI to AD. 52 A higher frequency of the ε-4 allele observed in patients with primarily amnestic MCI further suggests an increased risk of conversion to AD in this subgroup. 53 These findings are in accordance with results reported by Fagan et al, who showed that baseline fludeoxyglucose positron emission tomography measurements and episodic memory loss predicted the rate of conversion from MCI to AD, whereas the p-tau181p/Aβ1-42 ratio predicted further cognitive decline.…”
mentioning
confidence: 94%